Climate projections over the Antarctic Peninsula region to the end of the 21st century. Part 1: cold temperature indices - Chyhareva, A.; Krakovska, S.; Pishniak, D. (Український антарктичний журнал, 2019)
Objective. This paper deals with an estimation of the climate change at the Antarctic Peninsula region. During last decades, the most significant warming is observed in Polar regions, particularly in the Antarctic Peninsula region, where the Ukrainian Antarctic Akademik Vernadsky station is located. Therefore, the providing of the complex estimation of climate change trend is an important task for the region. These changes are taking place nowadays and will happen in the future. So, the main objective of the study is to estimate changes of climate characteristics in the Antarctic Peninsula region in the 21st century, based on calculation of the relevant climate indices. The projections of the temperature and precipitation characteristics in the Antarctic Peninsula region and Akademik Vernadsky station area for RCP4.5 and RCP8.5 scenarios are the objects of the research. Стаття присвячена оцінці змін, що відбуваються в районі Антарктичного півострова. Впродовж останніх десятиліть найсуттєвіше потепління в кліматичній системі спостерігається в полярних регіонах, зокрема в районі Антарктичного півострова, де розташована Українська антарктична станція «Академік Вернадський». У зв’язку з цим необхідно забезпечити кращу комплексну оцінку тенденцій кліматичних змін, які вже зафіксовані та прогнозуються в майбутньому. Мета дослідження — оцінити зміни кліматичних характеристик в регіоні Антарктичного півострова в ХХІ столітті, на основі обчислення відповідних кліматичних показників. Об’єкт дослідження: проекції характеристик температури повітря та режиму зволоження в районі Антарктичного півострову та Української антарктичної станції «Академік Вернадський» за сценаріями RCP4.5 та RCP8.5 (Representative Concentration Pathway, RCP, Траєкторії репрезентативних концентрацій). Методами дослідження є чисельне моделювання та статистичний аналіз даних регіональних кліматичних моделей.